(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an overview of articulatory and acoustic phonetics, focusing on the interaction between the physical production of sounds (articulation) and their acoustic properties. It begins by detailing articulatory phonetics, explaining how different speech organs (such as the lips, teeth, tongue, and glottis) contribute to producing sounds through various manners and places of articulation, like stops, fricatives, and nasals. It then explores acoustic phonetics, focusing on key acoustic features—frequency, amplitude, and duration—and their role in sound perception. Special emphasis is given to formants, resonant frequencies critical in distinguishing vowel sounds. The article also examines the interplay between articulatory and acoustic features, underscoring their importance in speech perception. The practical applications, ranging from linguistics to speech therapy and forensic phonetics, highlight the relevance of these concepts across multiple fields, demonstrating the scientific complexity behind human speech production and perception.